The measurement of dietary species richness reveals that a higher consumption of dietary fibre, fish, fruits and vegetables, is associated with greater food biodiversity in UK diets - Magaly Aceves-Martins; Anneli Löfstedt; Carlos Francisco Moreno-García; Elizabeth H Zandstra; Anne J Wanders; Baukje de Roos (Public Health Nutrition)
Abstract